Yo-Yo IR2 testing of elite and sub-elite soccer players: Performance, heart rate response and correlations to other interval tests - Ingebrigtsen, J.; Bendiksen, M.; Bredsgaard Randers, M.; Castagna, C.; Krustrup, P.; Holtermann, A. (Journal of Sports Sciences, 2012)
We examined performance, heart rate response and construct validity of the Yo-Yo IR2 test by testing 111 elite and 92 sub-elite soccer players from Norway and Denmark. VO2max, Yo-Yo IR1 and repeated sprint tests (RSA) (n = 51) and match-analyses (n = 39) were also performed. Yo-Yo IR2 and Yo-Yo IR1 performance was 41 and 25% better (P < 0.01) for elite than sub-elite players, respectively, and heart rate after 2 and 4 min of the Yo-Yo IR2 test was 20 and 15 bpm (9 and 6% HRmax), respectively, lower (P < 0.01) for elite players. RSA performance and VO2max was not different between competitive levels (P > 0.05). For top-teams, Yo-Yo IR2 performance (28%) and sprinting distance (25%) during match were greater (P < 0.05) than for bottom-teams. For elite and sub-elite players, Yo-Yo IR2 performance was correlated (P < 0.05) with Yo-Yo IR1 performance (r = 0.74 and 0.76) and mean RSA time (r = -0.74 and -0.34). We conclude that the Yo-Yo IR2 test has a high discriminant and concurrent validity, as it discriminates between players of different within- and between-league competitive levels and is correlated to other frequently used intermittent elite soccer tests.